Making of a Solar Energy Light Optimization Monitoring System Using Current Sensor on Personal Computer Interface - Oki Petrus Hutauruk (Saintia Fisika, 2013)
Use of a solar energy in Indonesia has a very good prospect, it is seen from the daily radiation at 4.5 kWh/m2/day. The author then tries to realize a tool that can set the direction of the solar cell panel always follows a shift from a light source that will be a source of electrical energy. The purpose of this research instrument is as a driver DC servo motor to control the motion of solar cell panels, the controller when any degree of DC servo motor to move the solar cell panel, time measurement and switching controller for still panel to the moving panel, and send serial data to a PC using AVR microcontroller ATMega 8535. Solar cell panels that are used have a maximum output power 0,3 Watt with current sensor type ACS712ELC-20A as a current sensing to measure the electrical power generated by the solar cell panel. Then the ADC resolution as an approximation of each bit signal going into the AVR microcontroller ATMega 8535 is about ± 4.89 mV/bit with the energy optimization by these two solar cell panels is 0,191 kWh and the precision angle of DC servo motor is 10 / 0,67 seconds. Furthermore, these data will be shown to the display PC into a graphical form through visual programming language Borland Delphi 7.0.